SOSIALISASI ETIKA PENGGUNAAN MEDIA SOSIAL DI KALANGAN REMAJA DESA BABOKERONG, KECAMATAN NAGAWUTUNG, KABUPATEN LEMBATA - Timu, Rose Virgine Ina; Waru, Felinsia; Welin, Elisabeth Date Masan; Ratumakin, Paulus Adrianua Kopong Liat; Lawalu, Stephanie Perdana Ayu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This service discusses the ethics of using social media among teenagers in Babokerong Village, Nagawutung Sub-district, Lembata Regency. The background is the development of information technology that affects the way teenagers use social media, but their understanding of digital ethics is still low. The aim was to understand the views, thoughts, and behaviors of teenagers regarding social media ethics and the factors that influence them. The method used was socialization on the ethics, dangers, and legal sanctions of social media, followed by discussion and reflection. The results showed an increase in adolescents' knowledge and successful analysis, and recommended educational strategies based on local wisdom.